Global Value Chains in Economic Theory: Disruption or Continuity of the Center-Periphery Matrix in Light of the History of International Trade? (2024)
The present work aims to examine the apparent benefits and effects of free trade based on the dynamics of the former General Agreement on Tariffs and Trade (GATT) and its successor, the World Trade Organization (WTO). The eminently ideological nature of the tax premises is denounced according to which its effects are intrinsically beneficial for developing and underdeveloped economies in the generality of the assumptions.  In this sense, an attempt is made to demonstrate that the reference institutions have consistently perpetuated the drifts that the “center-periphery” analytical model historically denounced to the latter's detriment.  The methodology used has involved a literature review of the GATT system and the international trade framework of the WTO, based on a critical examination of these in relation to the theses of both classical and contemporary structuralist economics. The study's results indicate that the multilateral trade system, along with the trade policies of hegemonic nations, through the functioning first of the GATT and then of the WTO, has resulted in endemically detrimental effects for peripheral economies. In this sense, the implications of this research suggest the need for a reexamination, both at the national and interregional levels, of the currently inequitable terms governing international trade, along with a more active promotion, at both levels, of development policies that prove to be beneficial for economically disadvantaged states.